Interactions of dietary fat with the gut microbiota: evaluation of mechanisms and metabolic consequences - Mokkala K.; Houttu N.; Cansev T.; Laitinen K. (Elsevier, 2022)
The current scientific literature proposes that both the amount and type of dietary fat modulate homeostasis of the gut microbiota; disturbances in homeostasis may have metabolic consequences with potentially serious clinical manifestations. The evidence for interactions between dietary fat and gut microbiota has been mostly derived from animal studies, but there is now also evidence emerging from human studies. We will review the current literature on how dietary fat influences the gut microbiota, particularly focusing on the type of fat. Mechanisms detailing how this crosstalk may impact on host metabolism and health will also be discussed. Some studies have reported somewhat controversial findings and therefore we will evaluate critically which possible aspects should be considered when interpreting current and planning further studies to explore the diet-microbiota crosstalk and its metabolic and clinical implications for the host.